Combined Topical and Oral Antimicrobial Therapy for the Eradication of Methicillin-Resistant Staphylococcus aureus (Mrsa) Colonization in Hospitalized Patients. (1st October 2002) - Fung, Scott K; Louie, Marie; Simor, Andrew E
Abstract : OBJECTIVE: How to eradicate methicillin-resistant Staphylo-coccus aureus (MRSA) colonization in hospitalized patients is uncertain. We reviewed our experience with MRSA decolonization therapy in hospitalized patients. SETTING: An 1100-bed, university-affiliated tertiary care teaching hospital in Toronto, Ontario. DESIGN: Retrospective chart review of 207 adult inpatients with MRSA colonization hospitalized between February 1996 and March 1999. INTERVENTIONS: All patients with MRSA colonization were assessed for possible decolonization therapy with a combination of 4% chlorhexidine soap for bathing and washing, 2% mupirocin ointment applied to the anterior nares three times/day, rifampin (300 mg twice daily) and either trimethoprim/sulfamethoxazole (160 mg/800 mg twice daily) or doxycycline (100 mg twice daily). This treatment was given for seven days. RESULTS: A total of 207 hospitalized patients with MRSA colonization were identified and 103 (50%) received decolonization therapy. Patients who received decolonization therapy were less likely than untreated patientsto have intravenous (P=0.004) or urinary catheters (P<0.001), or extranasal sites of colonization (P=0.001). Successful decolonization was achieved in 90% of the 43 patients who were available for at least three months of follow-up. CONCLUSIONS: Combined topical and oral antimicrobial therapy was found to be effective in eradicating MRSA colonization in selected hospitalized patients, especially those without indwelling medical devices or extranasal sites of colonization.